Mesenchymal stromal cell-laden hydrogels in tissue regeneration: insights from preclinical and clinical research - Barbon, Silvia; Rajendran, Senthilkumar; Banerjee, Antara; Parnigotto, Pier Paolo; De Caro, Raffaele; Macchi, Veronica; Porzionato, Andrea (Frontiers in Pharmacology, 2025)
Hydrogel-based delivery systems have emerged as a promising strategy to enhance the therapeutic efficacy of mesenchymal stromal cells (MSCs) in regenerative medicine. These biomimetic platforms provide a three-dimensional microenvironment that recapitulates key features of native extracellular matrix, supporting MSC viability, retention, and function upon transplantation. Beyond acting as passive carriers, hydrogels can be engineered with tunable biochemical and mechanical properties to modulate MSC behavior, including their differentiation potential, immunomodulatory activity, and paracrine signaling. Recent advances include the development of “smart” hydrogels responsive to physiological stimuli, enabling controlled release of encapsulated cells or bioactive molecules in response to local cues. Preclinical studies have demonstrated enhanced tissue repair in diverse pathological contexts, including musculoskeletal, cardiovascular, gastrointestinal, dermal, and neural injuries. Importantly, translation to clinical settings is being facilitated by the use of xeno-free, good manufacturing practices (GMP)-compliant components such as platelet derivatives and synthetic polymers. Selected early-phase clinical trials support the feasibility, safety, and therapeutic potential of MSC-laden hydrogels, although further studies are required to optimize delivery parameters and regulatory compliance. This review summarizes current progress in hydrogel-MSC systems across application areas, emphasizing design principles, preclinical outcomes, and translational challenges, with the aim of guiding future developments in stem cell-based tissue regeneration.